AM and FM difference limens - SĘK, A.; OZIMEK, E. (Archives of Acoustics, 1994)
This paper reports two basic experiments aimed at determining difference limens (DLs) for amplitude and frequency modulation as a function of the modulation indices (m, β) modulation frequency and sound pressure level of the modulated signals. Two types of modulator were used. The first one was the sinusoidal signal. In this case the simplest (sine by sine) amplitude and frequency modulation was considered. In the second case the modulator had a constant frequency but its amplitude was randomly changed with mean 0 and standard deviation σ. In a two-alternative forced choice task just noticeable differences of modulation intensity were measured. It was found that AM and FM difference limens increase with the increase of modulation indices of the reference signals. Additionally, it was shown that the difference limens were almost independent of the modulation frequency. They were also independent of the type of modulator used in the investigations.